Employee turnover intentions, organisational commitment and job satisfaction in a post-merger tertiary institution : the case of the University of Limpopo - Masemola, Sheweng Emily (University of Limpopo (Turfloop Campus), 2011)
The change or transformation of higher education institutions in South Africa (SA) was mandated by the government, as a response to address past disparities that prevailed as a result of the apartheid government. These disparities, included inter alia, improving access to higher education institutions, improving staff and student equity and improving the quality of higher education throughput. The merger of higher education institutions in SA, like any other institution in another country that had undergone a similar form of change, mostly share the similar experiences, especially if the mergers are mandated by the government. The fundamental issue and the inspiration of the study is the impact of the merger, whether directly or indirectly, on employees’ job satisfaction, organisational commitment and intention to leave. The target population of the study was the university of Limpopo employees, clustered into three categories, viz. the academic, administrative and support services personnel. The study used a random sampling method. A questionnaire, with a combination of closed and open ended questions, was used to collect data. The results indicated that the respondents were not satisfied with their jobs had low organisational commitment and some intentions to leave the employ of the university. However, they indicated that the merger had very little effect on these results.
Thesis (MBA) -- University of Limpopo, 2011
Keywords: Personnel management; Job satisfaction; Job satisfaction -- South Africa; Employee retention